(untitled) - Bandyopadhyay, P.C. (New Delhi, 2007)
Contents: Biological factors of soil fertility; soil nutrient cycling; soil fertility management; analysis of soil fertility issue
Keywords: Soil fertility,Fertilizers,Sustainable agriculture,Nông nghiệp bền vững